2020
DOI: 10.1111/os.12822
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Postoperative Effects between Medial Pivot Prosthesis and Posterior Stabilized Prosthesis

Abstract: Objective: To compare the postoperative inflammation and pain response between medial pivot (MP) and posterior stabilized (PS) prostheses among total knee arthroplasty (TKA) patients. Methods: A prospective cohort study was conducted from January 2019 to May 2019 at the Affiliated Hospital of Qingdao University. The study included patients diagnosed with stage III or IV Kellgren-Lawrence knee osteoarthritis (KOA) who had failed conservative treatment, had undergone no previous knee surgeries, had varus substan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…A total of 13 studies reported ROM [ 4 , 5 , 8 , 11 , 18 , 19 , 21 25 , 30 , 32 ]. Since high heterogeneity was indicated ( I 2 = 77%, P < 0.1), sensitivity analyses were conducted.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 13 studies reported ROM [ 4 , 5 , 8 , 11 , 18 , 19 , 21 25 , 30 , 32 ]. Since high heterogeneity was indicated ( I 2 = 77%, P < 0.1), sensitivity analyses were conducted.…”
Section: Resultsmentioning
confidence: 99%
“…After the two researchers read the title and abstract, they further ruled out 563 irrelevant studies. Finally, the researchers reviewed the full text of the remaining 45 studies and determined that 19 studies could be included in the final meta-analysis [4,5,8,11,[18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Figure 1 shows the flow chart.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total knee arthroplasty (TKA) is an effective surgical procedure for end-stage knee osteoarthritis in terms of functional restoration of the knee and pain relief [ 1 , 2 , 3 , 4 ]. Despite this, over 20% of patients complained about continuous pain and dissatisfactory function [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ball-and-socket medial compartment provides knee stability, and the relatively flat surface on the lateral compartment allows for greater anterior-posterior translation. Multiple studies have reported superior clinical patient outcomes in MP-TKA compared to PS-TKA [ 1 , 15 , 16 , 17 , 18 ]. In contrast, some other studies have shown no difference between the two groups [ 2 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%